Studies of Anti-arrhythmic and Hypercholesterolemic Activities of Ayurvedic Preparation Lauhasab in Rat Model - Rezwan, Refaya; Zafar, Sharmin; Chowdhury, Abu Asad; Kabir, Shaila; Amran, Mohammad Shah; Rashid, Mohammad Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Lauhasab, an Ayurvedic preparation, is widely used in anemia and cardiovascular diseases. Despite its claim as a cardio-tonic there is paucity of studies on pharmacological activities and toxicities. In this study, the anti-arrhythmic effect and impact on lipid profile were evaluated. Rats were pretreated with 0.28 and 2.8 ml/kg body weight of Lauhasab for 35 days and electrocardiographic tracings were recorded and analyzed to determine heart rate and occurrence of arrhythmia. Electrocardiogram recorded before digoxin administration showed significant decrease in mean heart rate along with longer duration of bradycardia than in digoxin control group after 35 days of chronic pretreatment with both doses of Lauhasab. In animal experiments, various arrhythmias were observed after intraperitoneal injection of digoxin. Lauhasab decreased the duration and delayed onset of time of various arrhythmias. It showed significant increase in cholesterol and triglyceride levels in a dose dependent manner. It can be concluded that Lauhasab possesses significant anti-arrhythmic activity against digoxin-induced arrhythmia. It also revealed hyperlipidemic effects. Dhaka Univ. J. Pharm. Sci. 16(1): 95-105, 2017 (June)